Improving Access to Justice: Do Contingency Fees Really Work? - Hutchinson, Allan C. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2019)
While not touted as a universal panacea for access problems, contingency fees have received general praise as an important and justice-improving initiative.  By back-loading the payment of legal fees, the assumption is that the interests of clients and litigants will be better served.  I challenge that received wisdom.  While the rise of contingency fee agreements between lawyers and clients has increased the number of people who can afford lawyers and make successful claims, the more challenging issue is whether that increase is being achieved at too high a price to clients and litigants – while more people are able to bring a case, which they could not otherwise have done, they will be receiving far less than they might actually be entitled to.  In short, do contingency fees work as much or more to the advantage of lawyers than clients?  I suggest not.